Morpho-Histological Study of the Thymus of Broiler Chickens During Post-Hashing Age - Tarek , Khenenou; Mohamed, Melizi; Omar, Bennoune; Hassina, Benzaoui (International Journal of Poultry Science, 2011)
The study of morphometric and histologic evolutions of the Thymus during 28 weeks of post-hashing age, realized on 86 subjects of broiler chicken they permitted to collect information about the morpho-histological aspect according to their post-hashing age; showed the size and the weight of the Thymus which reach their maximum at the 2nd week of age and the physiologic involution phenomena. These variations are in close relationship to the sexual maturity. These results can be used in the diagnosis of viral disease such as the Gumboro disease, Marek disease, Mycotoxicose.